Towards a knowledge management framework for disaster management in Malaysia - Mohd Rodzi M.Z.; Zakaria N.H.; Ahmad M.N.; Yahya H. (IOS Press, 2023)
In the last few decades, Malaysia has experienced various disasters including man-made and natural disasters. These disaster occurrences led to significant casualties in terms of the death toll and loss of assets. Harnessing the knowledge from individuals and agencies involved in disaster relief operations is a crucial step that requires the implementation of knowledge management (KM) as the potential solution to curb the impact of disasters. Managing a large amount of knowledge needs a framework that is able to govern the necessary knowledge processes and function as the tool for effective decision-making and forecasting. Based on the existing research on KM frameworks, this paper primarily proposes a KM framework for disaster management in Malaysia that is comprised of knowledge processes, namely, audit, transfer, integrate and dissemination, supported by critical success factors for more effective results. The framework will subsequently form the basis for the development of our "enterprise" knowledge management system (KMS) known as the Enterprise Knowledge Management System for Flood Management (EKMS4FM). © 2014 The authors and IOS Press. All rights reserved.